INFECCIÓN EXPERIMENTAL DE CERDOS DE UN MES DE EDAD CON ESPORAS DE Enterozytozoon bieneusi - Alvarado G., Jéssica (2009)
Human microsporidiosis has been considered a disease of the VIH positive patients or other patients with immunosupression. At present, it is known that microsporidiosis affects not only these patients but also the immunocompetent. The most common species is the Enterocytozoon bieneusi. The present study demonstrates the experimental oral infection of one-month-old piglets with spores of E. bieneusi. Nine piglets from a commercial farm with very low risk of infection by this parasite were used. Two staining techniques were utilized for the diagnosis of the parasite: Tricromic Blue Stain (in fecal samples) and Silver Stain (in intestinal wall). Spores of E. bieneusi were observed in feces and intestinal sections of all animals. The estudy showed that pigs of one month of age are susceptible to the infection with spores of E. bieneusi and therefore, could be considered as experimental model in the study of the human microsporidiosis caused by E. bieneusi.